Das Programm des Ökumenischen Rates der Kirchen (ÖRK) zur Bekämpfung des Rassismus (PCR), afrikanische Volksrepubliken und die deutschen Kirchen - Besier, Gerhard (Kirchliche Zeitgeschichte, 1996)
The World Council of Churches' Programme to Combat Racism (PCR) was aimed not merely to combat racism on a world-wide basis. In fact, many churchmen in the so-called "First", "Second" as well as the "Third World" indulged in the hope that this Programme would be an effective weapon with which at least to modify the alleged "unjust" "capitalist system" of the western world, which they saw as the root cause for imperialism and racism. In the communist-dominated states of eastern Europe, those officials responsible for church relations welcomed this critical approach from so many churchmen towards the western social system. Indeed this attitude only strengthened their previous reservations, and led them to intensify their contacts with the liberation movements in the "Third World". At the same time they sought to co-ordinate the church opposition forces in the Geneva head office of the World Council, by trying to influence the selection of new appointees to the World Council's staff in Geneva. Thereby the balance of forces in the WCC should be altered in favour of the "Second" or "Third World". If we look at the specific cases of Mozambique and Angola, we can see that the East German regime's strategy of using its religious tactics as one element of its foreign policy was rather successful. Similarly, at home, this regime sought to contrast the prevalence of racism in the western world to the "humanistic" conditions of life in the socialist countries, and thereby reinforce their propaganda campaign against capitalism. Only the collapse of this regime, as well as of the whole communist block, forestalled the long-planned expansion of this strategy to Namibia and South Africa. In fact only the lack of adequate financial resources, rather than any hindrances in the field of personnel or propaganda resources, handicapped the realization of this otherwise successful policy of advancing the regime's political aims through the infiltration of the world church bodies, such as the World Council of Churches.
Keywords: Geschichte 1970-1989; Deutschland; Südafrika; Antirassismusprogramm; Evangelische Kirche